Radiation Perception and Knowledge among Patients at Referral and District Hospitals in Rwanda - Louise Tuyishime; Yves Usabyimbabazi; Eric Kirezi; Adam Moyosore Afodun; Mecthilde Mukangendo; Azeez Omoniyi Adeoye; Mustapha Akajewole Masud (Janaki Medical College Journal of Medical Science, 2024)
Background and objectives: The prevalence of cancer is on the rise, and radiation therapy is an essential part of treatment. However, patients frequently have a limited grasp of radiation therapy, which can result in anxieties and misconceptions. This study's main purpose was to investigate patients' radiation perceptions at both referral and district hospitals in Rwanda by examining patients’ knowledge, attitudes, and concerns related to medical radiation. Materials and Methods: The study employed a quantitative approach where data were collected through structured questionnaires and administered to a diverse sample of patients at referral and district hospitals in Rwanda. The quantitative data collected was analyzed using IBM SPSS software, version 27.0, which was released in 2015. The relationship between the variables was measured using a chi-square test from SPSS. Descriptive statistics were employed, utilizing percentages and frequencies. Results: Findings revealed significant misconceptions among patients, with many lacking awareness of radiation dangers despite undergoing radiological procedures. Factors such as education level influence knowledge levels with higher-educated individuals rating their understanding more positively. Conclusion: Significant exposure differences, knowledge and awareness gaps among selected respondents with varying educational levels regarding medical radiation dangers were found in this study conducted on radiation perceptions among patients in Rwandan hospitals.